1995
DOI: 10.1111/j.1600-0447.1995.tb09752.x
|View full text |Cite
|
Sign up to set email alerts
|

Blood pressure as a risk factor for depression in elderly people: a prospective study

Abstract: A total of 1070 men and women aged 65 years and over living in the community in Liverpool were interviewed using the Geriatric Mental State. Diagnoses of depression at case and subcase level were made using the GMS-AGECAT package from an initial interview and at follow-up three years later. Data relating to blood pressure at year 0 was available on 748 subjects. Men not taking anti-hypertensives or antidepressants with diastolic blood pressure greater than 85 mmHg were significantly less likely to be subcases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…Conversely, other studies in broad age range cohorts [6,34,35] and one in elderly individuals [36] failed to exhibit any association between BP and depression or psychological symptoms. Moreover, several studies in younger adults [12][13][14] suggested that psychological disturbances were predictors of incident hypertension and a study in elderly individuals found an association between undetected hypertension and depression [37].…”
Section: Discussionmentioning
confidence: 85%
“…Conversely, other studies in broad age range cohorts [6,34,35] and one in elderly individuals [36] failed to exhibit any association between BP and depression or psychological symptoms. Moreover, several studies in younger adults [12][13][14] suggested that psychological disturbances were predictors of incident hypertension and a study in elderly individuals found an association between undetected hypertension and depression [37].…”
Section: Discussionmentioning
confidence: 85%
“…Four cross-sectional (12-15) studies and a prospective study (16) showed inverse associations between BP and depressive symptoms. Another prospective study found no association (17). In contrast, three cross-sectional studies found a positive association between hypertension and depression (18)(19)(20).…”
Section: Discussionmentioning
confidence: 92%
“…However, in epidemiological studies, observations of the relationship between BP and depression have been inconsistent (12)(13)(14)(15)(16)(17)(18)(19)(20). Because the white-coat phenomenon has been observed frequently in all psychological types but especially in types having depressive symptoms (21,22), we have considered that BP measured in nonmedical settings is important in assessing the relationship between BP and depressive symptoms among the geriatric population.…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, some studies have indicated that low blood pressure is associated with various somatic and psychological symptoms. 5 10-12 Four of six geriatric studies, using standardised screening inventories for depression, found an association between low blood pressure and depression, 6 13-15 one study found no association, 16 whereas a recent study found an association between hypertension and depression. 17 However, the design and findings in some of the studies have been contested.…”
mentioning
confidence: 99%